Determinants of foreign direct investment in five selected West African countries - Muhammad, Ishaq Auwalu (2015)
This study examines the determinants of foreign direct investment inflows (FDI) in West African Countries (WACs) for the period 1998-2013. Analysis of the study used secondary data which obtained from World Bank Development indicators, World Bank Governors Indicators, United Nations Conference on Trade and Development, Transparency International, and Heritage Foundation. In this study, Dunning’s (1980) eclectic paradigm was used but with modification to include some additional variables. Empirically, Fixed Effects Model (FEM) was suggested by the results of Hausman’s specification test as a preferable model in the estimation. The finding shows that corruption does not influenced the level of FDI inflows into WACs. Specifically, foreign investors were rather discouraged by both corruption and poor regulatory institutions. Other factors like market size, inflation and trade openness of the economy were also found to be positively significant. The findings suggests that governments in WAC need to reform their institutions in order to attract more FDI and benefited from the positive spill overs that accompany FDI inflow into a country. With regards to FDI determinants, the empirical result indicates that the domestic country potential market demand and trade openness are the main determinants of FDI inflows in WACs.